2022
DOI: 10.3390/ijerph192113937
|View full text |Cite
|
Sign up to set email alerts
|

“I Would Rather Take the Vaccine Than Undergo Weekly Testing”: Correlates of Health Workers’ Support for COVID-19 Vaccine Mandates

Abstract: This study examined the support for vaccine mandates and uptake among clinical and non-clinical staff at a tertiary hospital in northern Nigeria, focusing on variation of survey responses based on job position, socio-demographic characteristics, and perceived risk of infection with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Using an explanatory, sequential, mixed-methods design and deploying a pragmatic paradigm, 370 healthcare workers were administered structured questionnaires. This was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(60 reference statements)
1
2
0
Order By: Relevance
“…While the studies in our synthesis reported high vaccination rates in this subpopulation, we also found hesitancy and even to some extent, rejection of the vaccination mandate. Similar to our findings, low support for COVID-19 vaccine mandates was found in Nigeria [69], France [70], and Cyprus [71]. The most common reasons for this hesitancy were related to the safety of this "new" vaccine and also some distrust in the government or the reported results from large-scale randomized trials [72].…”
Section: Indirect Effect On Vaccination In Healthcare Workerssupporting
confidence: 76%
“…While the studies in our synthesis reported high vaccination rates in this subpopulation, we also found hesitancy and even to some extent, rejection of the vaccination mandate. Similar to our findings, low support for COVID-19 vaccine mandates was found in Nigeria [69], France [70], and Cyprus [71]. The most common reasons for this hesitancy were related to the safety of this "new" vaccine and also some distrust in the government or the reported results from large-scale randomized trials [72].…”
Section: Indirect Effect On Vaccination In Healthcare Workerssupporting
confidence: 76%
“…Hence one author stated "COVID-19 vaccine mandates for [HCWs] may ultimately be the only viable strategy for achieving an adequate level of vaccination among health care workers", especially for HCWs who were "on the fence", yet presented "modifiable barriers to vaccination"such as HCWs waiting for more long term safety data (Choi et al, 2022) (p.294). The call for mandatory vaccinations for HCWs cut across continents, with studies from low-or middle-income countries also recommending it given concerns over "vaccine hesitancy" (Badahdah et al, 2022;Iliyasu et al, 2022;Iwu et al, 2022;Singh et al, 2021) and the health challenge "hesitating" would unleash.…”
Section: What Is the Problem Represented To Be In The Expert Literatu...mentioning
confidence: 99%
“…Such policies may potentially interfere with a number of human rights, including the right to liberty, to work, education, bodily integrity, privacy, freedom of movement, freedom of assembly, and the right to equal treatment [2]. In December 2021, the Nigerian federal government declared a compulsory COVID-19 immunization for all employees of government [8]. This declaration by the government has been viewed by some Nigerians as a contravention of the fundamental rights of Nigerian citizens.…”
Section: Introductionmentioning
confidence: 99%